Risk factors and prophylaxis against invasive fungal disease for haematology and stem cell transplant recipients: an evolving field. Issue 12 (1st December 2016) - Douglas, Abby P.; Slavin, Monica A.
ABSTRACT: Introduction : Due to increasing intensity and complexity of therapies and longer survivorship, many patients with haematologic malignancy (HM) are at risk of invasive fungal disease (IFD). Mortality from IFD is high and treatment of an episode of IFD results in an excess length of hospital stay and costs and delays delivery of curative therapy of the underlying haematologic condition. Therefore, prevention and early recognition and treatment of IFD are crucial. Areas covered : Risk factors particular to certain HMs and haematopoietic stem cell transplantation, as well as those risk factors universal to all HM groups are examined. Expert commentary : Risk stratification identifies those patients who would benefit most from mould active versus yeast active prophylaxis and those who can be safely managed with monitoring and clinically driven interventions for IFD. This approach aids in antifungal stewardship.